Perpetration and victimization of emotional abuse and controlling behaviors in a sample of batterer intervention program’s participants: an analysis of stressors and risk factors - Solina-Saunders, Monica (Crime & delinquency, 2022)
The study employs a sample of 584 men and women referred to a multisite BIP and investigates IPV risk factors and stressors. The study also identifies unique risk factors and stressors in association with both IPV perpetration and IPV victimization. The findings show that women in the sample were more likely than men to report IPV victimization but the difference between the two groups is only marginally significant. Criminal thinking shows the most robust findings and is significantly associated with both IPV perpetration and IPV victimization. Mental health problems are consistently associated with both IPV perpetration and IPV victimization. The study’s findings are particularly relevant for the design and implementation of BIP that address participants’ needs based on gender.